Imperial Germany and War, 1871-1918 - Hughes, Daniel J., 1946-; DiNardo, R. L. (Book collections on Project MUSE., 2018)
"This erudite volume provides a fine-grain portrait of the Imperial German army from its greatest victory in 1871 to its final collapse in 1918. Written by two of the scholarly world's leading authorities, it offers meticulous research into the German sources, judicious verdicts on men and events, and a sweep broader than any previous work on the subject. Hughes and DiNardo have produced an indispensable book, one that will dominate the narrative on the German Army for decades"--